Microbiological contamination of vegetables produced in a rural community in the municipality of Januária-MG (Research, Society and Development, 2022)
The consumption of vegetables can expose consumers to the risk of several pathogenic microorganisms. This study aimed to evaluate the microbiological contamination of vegetables produced in a rural community in the municipality of Januária-MG. Two vegetable producing properties were selected, where samples of the produced vegetables and the water used for irrigation were collected. In the samples of vegetables and water, the count of total coliform bacteria, coliform bacteria at 45ºC and Escherichia coli bacteria were evaluated. The count of coliform bacteria in the samples of vegetables and water evaluated was above the limits determined by Brazilian legislation. The analysis of coliforms at 45ºC and E. coli bacteria serves as an indicator of fecal contamination, deficient hygienic sanitary conditions, in addition to the possible presence of pathogenic microorganisms. The high count of coliform bacteria observed in samples of vegetables and water used for irrigation suggests that these products may pose a risk to consumers' health.